Elemental World Cinema : Cinematic Entanglements of Earth, Fire, Water and Air - Luca, Tiago de; Mroz, Matilda (Contemporary Cinema, 2025)
This is the first book-length study on the relationship between cinema and the classical elements. It centres on earth, fire, water and air to offer new perspectives on the intersection of film and the nonhuman in a time of climate emergency. Mobilising a range of analytical frameworks, including early film theory, Indigenous epistemologies and environmental sciences, the essays in this collection trace the complex agencies of the elements as they intersect with the material properties of the cinematic image across fiction, animation, documentary and experimental film. In doing so, the book positions elemental cinema as a multifaceted process and experience that might encompass attempts to think with, alongside or even 'like' the elemental, all the while recognising the limitations of our anthropocentric systems of meaning.